Spanish modernism and the poetics of youth : from Miguel de Unamuno to La Joven literature - Harkema, Leslie (Toronto Iberic, 2017)
In Spanish Modernism and the Poetics of Youth: From Miguel de Unamuno to La Joven Literatura, Leslie J. Harkema analyzes the literature of the modernist period in Spain in light of the emergence of youth culture in the late nineteenth and early twentieth century.